Spatial Analysis of Rainfall Levels with the Incidence of Dengue Hemorrhagic Fever (DHF) in Central Java Province in 2019 - Rifka Putri Salma; Novita Anindia; Muhammad Hanif Fadhilah; Chiara Maharani; Izzah Dinillah; Khalisa Zahra; Nurmawaddah; Risdiyanti Arsyil; Yosephine Roma Intan; Raihan Rasyad Albiruni; Ema Hermawati; Al Asyary (UHAMKA Press, 2020)
Dengue Hemorrhagic Fever (DHF) is an acute viral infectious disease caused by the dengue virus. This disease cannot be transmitted directly from person to person, but through the bite of a female Aedes aegypti mosquito infected with the dengue virus, it can also be spread by other species, namely Aedes albopictus. Extraordinary Events (KLB) DHF usually occur in endemic areas and are associated with the presence of the rainy season. This study intends to find out whether dengue cases in all districts in Central Java Province have a relationship with rainfall levels during 2019. In this study, spatial analysis and statistical analysis methods were used on secondary data available online through literature studies from various references. Through the results of this study, it is known that there is no relationship between the number of dengue cases and the intensity of rainfall in Central Java Province in 2019.